Atypical functional connectome is associated with low reflective functioning in incarcerated adolescents - Derome, Mélodie; Morosan, Larisa; Heller, Patrick; Debbané, Martin (Frontiers in Psychiatry, 2025)
IntroductionWhile functional neuroimaging studies have reported on the neural correlates of severe antisocial behaviors, such as delinquency, little is known about whole brain resting state functional connectivity (FC) of incarcerated adolescents (IA). The aim of the present study is to identify potential differences in resting state connectivity between a group of male IA, compared to community adolescents (CA). The second objective is to investigate the relations among FC and psychological factors associated with delinquent behaviors, namely psychopathic traits (callous unemotional traits, interpersonal problems, and impulsivity), socio-cognitive (empathy and reflective functioning RF) impairments and psychological problems (externalizing, internalizing, attention and thought problems).Methods31 male IA and 30 male CA participated in 8 minutes resting state functional MRI. Network Based Statistics (NBS) was used to compare FC among 142 brain regions between the two groups. Correlation and regressions analysis were performed to explore the associations between FC and the self-reported psychopathic traits, empathy, RF, and psychological problems.ResultsCompared to the CA, the IA group presented significantly increased resting state FC in a distributed subnetwork including medial prefrontal, posterior and dorsal cingulate, temporal, and occipital regions. Both within the IA group and across the whole sample, increased mean connectivity of the subnetwork correlated with lower RF (RF uncertainty). Across the whole sample, the mean connectivity was associated with higher scores of externalizing problems and impulsivity dimension of psychopathy.DiscussionWhile extending the characterization of whole brain resting state FC in IA, our results also provide insights into the neurofunctional mechanisms linking low reflective functioning abilities to externalizing behavior during adolescence.